THE IMPORTANCE OF MASTERING MATHEMATICAL CONCEPTS IN SOLVING MATHEMATICAL PROBLEMS IN ELEMENTARY SCHOOLS - Fina Tazkiya (Kirana Publisher, 2023)
Teachers realize that mathematics is often considered a subject that is less desirable, feared, and avoided by most students. Various alternatives are used by teachers in learning mathematics, both the mathematical approach and the methods used so that students can master mathematical concepts and can solve problem solving problems. The purpose of this article is to describe the importance of mastering mathematical concepts in solving elementary math problems. Mastery of mathematical concepts is the basis for being able to solve mathematical problems with higher order thinking. In basic education students are directed to have cognitive abilities, namely analyzing (C4), evaluating (C5) and even creating (C6). These abilities are closely related to many of the questions that lead to solving mathematical problems. So that the teacher trains students to be able to solve mathematical problems, where students must have the ability to master mathematical concepts.